In situ analysis of tumor-specific CTL effector and memory responses elicited by tumor vaccination. - Schirrmacher, Volker (International journal of oncology, 1999)
In this study tumor-specific CTL effector and memory responses were analyzed in normal mice, in tumor bearing mice and in animals treated by active specific immunotherapy (ASI) with an autologous virus modified tumor vaccine. In the well defined DBA/2 mouse lymphoma model ESb, the tumor specific CTL response requires interactions of four different cell types and recognition of MHC class I and class II restricted tumor antigens either on host antigen presenting cells (APCs) or on the tumor cells. The most effective in situ activation of syngeneic tumor specific CTL can be generated within no more than 9 days by primary immunization in the ear pinna and restimulation in the peritoneal cavity. Here we describe modulatory effects of either cytokines or of virus infection of tumor stimulator cells during restimulation in the peritoneal cavity on the CTL memory response. The in situ peritoneal effector cell (PEC) response was augmented when Newcastle Disease Virus (NDV) was used to infect tumor cells which expressed the correct tumor associated antigen of the memory response but not when a third party tumor cell was infected and admixed. A response could also be augmented by co-administration of interferons-alpha, -beta or IL-2 and by pre-treatment with low dose cyclophosphamide. Therapeutic vaccination effects could be achieved in mice inoculated s.c. with this aggressive and metastatic tumor variant if the vaccine was given very early, i.e. 1-2 days after priming and when the vaccine was applied post-operatively, i.e. in situations of low tumor burden. A long-term CTL memory response could be demonstrated even two months after post-operative active specific immunotherapy with ESb-NDV vaccine.